(untitled) (Investigación y Desarrollo, 2020)
La televisión local además de informar, muchas veces se convierte en la única forma de expresión de la identidad y cultura de toda una localidad. El artículo profundiza en la realidad de la televisión local aludiendo a que es necesario velar para que la televisión local no pierda los contenidos de proximidad que la mueven y alimentan, pues son este tipo de medios de comunicación los encargados de potenciar la identidad cultural de las pequeñas comunidades y así mantener vivas las costumbres, lenguas e idiosincrasia de poblados que de otras manera se perderán ante los conteni- dos generalistas de las grandes urbes. Palabras claves: Televisión local, identidad, desarrollo, comunidad. ABSTRACT Technology in the cultural industries world determines new and continuous challenges. The arrival of the DVB-T has revolutionized the world of communication, not only the television, but also for the radio, the print media, adverti- sing and many actors linked to communicationsThe arrival of the DVB-T officially announced for 2017 in Chile, has become an avalanche technology that plagues the local television stations, which aree without the economic tools, legal and technological as to take part of the revolution and not victims of it. Then is time to get to know the fears, but also to reveal the opportunities that new technology brings to this type of radio station. Key Words: Local Television, identity, evolution, community.